Identification and Efficient Synthetic Method for Preparation of Cyclopentane-1,3-diol Impurity in Tafluprost Drug - Venkatanarayana, Muvvala; Mohana Reddy Jaggavarapu, Rama; Venkata Reddy, G.; Sharathbabu, H. (Asian Journal of Chemistry, 2020)
In present work, the isolation, synthesis and characterization of the identified triol impurity present in tafluprost is described. This investigation helps to avoid formation of impurity by control the reaction and its leads to improving high yields of tafluprost. The source of impurity was identified, due to over-reduction of lactone with diisobutyl aluminum hydride (DIBAL-H).